Treatment of idiopathic sudden sensorineural hearing loss with press needle - Qin, Feng; Guo, Siquan; Yin, Xiuwen; Guo, Jinbao; Lu, Xiaoyu; Ma, Jing (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the effects of conventional therapy and press needle combined therapy on idiopathic sudden sensorineural hearing loss. Method: The retrospective case-control study was conducted from December 2023 to January 2024 at Department of Otorhinolaryngology, Changzhou Third People’s Hospital, China, and comprised patients with idiopathic sudden sensorineural hearing loss ISSNHL admitted from September 2021 to November 2023. The patients were divided into control group CON in which conventional therapy was used, and the PN group in which the press needle therapy was given additionally. The groups were compared with respect to clinical effects. Data was analysed using SPSS 20. Results: Of the 297 patents, 143(48%) were in group CON and 154(52%) were in group PN. There was no difference between the groups in terms of age and gender (p>0.05). The PN group showed greater changes in pure-tone audiometric thresholds than the CON group (p<0.05), and the difference was more significant in high-frequency hearing loss patients (p<0.05). Conclusion: The addition of press needle therapy showed better therapeutic recovery in idiopathic sudden sensorineural hearing loss patients compared to the conventional therapy alone. Key Words: Acupuncture, Hearing loss, Sensorineural, Case-control study.